Ida Applebroog : 1976 > 2002 : are you bleeding yet ? - La maison Red; Lignel, Benjamin; Prose, Francine (New York : la maison Red, 2002)
Edited by Benjamin Lignel, this distinctive book lays out Ida Applebroog's exhibition career, starting with her first New York solo show in 1976 at the Woman's Interart Center, through twenty-five years of exhibitions at Ronald Feldman Fine Arts, at site-specific installations, museums, storefronts, and billboards. Refusing to label her work other than "generic", this book bears out Applebroog's adept handling of the diverse methods she has employed in her art : self-published books, film and video, vellum manuscript pages, watercolors, and her distinctive multi-panel paintings. An introduction by National Book Award Nominee Francine Prose presents the intricacies of viewing the deceptively simple scenes depicted in Applebroog's work. "Ida Applebroog : Are You Bleeding Yet ?" includes excerpts from interviews, novels, essays and reviews from 40 contributors, including leading critics and curators.
bibliog. p.284-291
coll., prijzen, biog. p.292-293
Engels
boek
Keywords: Applebroog, Ida